A Schoolyard to Play - Guerra, H.; Cortes, N.; Santos, C. (Open Schools Journal for Open Science, 2020)
This is an entrepreneurship project that promotes awareness, as its main action is to make the school more appealing. Students have raised this problem and identified the main goal of improving the schoolyard spaces. Problems were surveyed and solutions presented, with the focus of intervention in green spaces, new paintings, and organization of leisure spaces. Contacts were initiated with different stakeholders, for the potential implementation of the solutions found in this project.